Forming method of strip-shaped carrier, preparation method of metal-loaded catalyst, catalyst and application thereof
Through a preparation method of a strip-shaped composite metal oxide hydrogen peroxide decomposition catalyst suitable for industrial production, the problem of insufficient catalyst molding in the prior art is solved, and efficient filling of catalysts and hydrogen peroxide decomposition in industrial fixed beds are realized. Good performance in the reaction.
Patent Information
- Application Number
- CN202310958467.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-01
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-08-01
AI Technical Summary
It is difficult to effectively form metal oxide catalysts in the prior art, especially in the demand for industrial fixed bed loading. The strength and catalytic activity of the catalyst are insufficient, making it difficult to meet the requirements of industrial applications.
A method for preparing a strip-shaped composite metal oxide hydrogen peroxide decomposition catalyst suitable for industrial production is adopted, including a support preparation process and a support impregnation process of metals. The carrier preparation process includes strong mixing of raw materials, rolling into blocks, extruding strip forming, drying and health preservation and high-temperature roasting; the carrier impregnation process includes drum impregnation, high-temperature drying, high-temperature roasting, rolling pelletizing and vibration screening to remove powder.
The prepared catalyst has excellent side pressure strength, meets the filling needs of industrial fixed beds, and has a good catalytic decomposition effect on low concentrations of hydrogen peroxide at low reaction temperatures, extending the life of the catalyst.
Abstract
Description
Technical Field
[0001] The present invention relates to a method for forming a carrier, a method for preparing a catalyst, a catalyst and applications thereof, and more specifically, to a method for forming a strip-shaped carrier, a method for preparing a metal-loaded strip-shaped hydrogen peroxide decomposition catalyst, the obtained catalyst and applications thereof in hydrogen peroxide decomposition. Background Art
[0002] The demand for hydrogen peroxide has increased significantly in various industries. For example, it is used for bleaching in the papermaking and textile fields to obtain pulp and fiber with satisfactory and stable whiteness; it is used for cleaning silicon wafers and etching circuit boards in the electronics industry; it is used for antiseptic, disinfection, aseptic packaging, etc. in the food industry; it is used to treat wastewater containing organic matter in the environmental protection field, greatly reducing the chemical oxygen demand (COD) of wastewater and meeting the requirements for wastewater discharge. Hydrogen peroxide has excellent oxidation performance, and its reduction product is water, which is non-toxic and harmless and does not introduce impurities into the system. Compared with traditional oxidants, it has significant advantages in environmental friendliness and economy. Especially after the advent of titanium silicalite (TS-1) and the realization of industrial production, it and hydrogen peroxide form a mild and efficient catalytic oxidation system, which shows good activity and selectivity in the hydroxylation of benzene and phenol, the epoxidation of olefins, the ammoximation of cyclohexanone, and the oxidation of amines and saturated alkanes.
[0003] However, during the above oxidation reaction, the conversion rate of hydrogen peroxide is usually maintained between 97% and 99%, so that the reaction product still has a residual mass fraction of 0.05% to 0.5% hydrogen peroxide. This part of hydrogen peroxide forms an easily explosive organic peroxide with organic matter in the subsequent separation process, and may also decompose and release oxygen by itself, affecting the safe and continuous operation of the device. Therefore, from a safety perspective, it is necessary to use a hydrogen peroxide decomposition catalyst to catalytically decompose it. The most common hydrogen peroxide decomposition catalyst is a metal oxide, among which manganese oxide is the most common. For example, CN110240203A discloses a method for preparing a manganese oxide catalyst. However, metal oxide catalysts need to be loaded and used in industrial reactors such as fixed beds, so such catalysts need to be formed to meet the filling requirements of fixed beds or other reactors. At present, there are few reports on the molding technology for metal oxide catalysts. Although CN114471591A discloses a strip-shaped decomposition catalyst, it does not disclose a specific molding method. Summary of the invention
[0004] The inventors have found that in the preparation process of various catalyst moldings, the molding steps, molding equipment and process routes have a significant impact on the strength and catalytic activity of the catalyst. The preparation of molded catalysts that can meet the requirements of industrial applications, such as the filling requirements of industrial fixed beds and other reactors, is a challenge.
[0005] With respect to hydrogen peroxide decomposition, the object of the present invention is to provide a method for preparing a strip-shaped composite metal oxide hydrogen peroxide decomposition catalyst suitable for industrial production. The catalyst prepared by the method has excellent lateral pressure strength and meets the filling requirements of an industrial fixed bed. When the catalyst is applied to a hydrogen peroxide decomposition reaction, it has a good catalytic decomposition effect on low-concentration hydrogen peroxide at a low reaction temperature.
[0006] Therefore, the first aspect of the present invention provides a method for preparing a strip-shaped composite metal oxide hydrogen peroxide decomposition catalyst suitable for industrial production, comprising a carrier preparation process and a carrier impregnation metal process; characterized in that:
[0007] The carrier preparation process includes five units: strong mixing of raw materials, rolling into blocks, extrusion molding, drying and curing, and high-temperature roasting; wherein the strong mixing of raw materials is carried out using a drum-type strong mixer with a rotor;
[0008] The carrier impregnation process includes five units: drum impregnation, high temperature drying, high temperature roasting, rolling granulation, and vibration screening to remove powder.
[0009] In the carrier preparation process, the raw materials are vigorously mixed by mixing the dry powder materials in a drum-type intensive mixer for 20 to 30 minutes under the conditions of a rotor speed of 80 to 120 r / min and a drum speed of 60 to 100 r / min; in the drum-type intensive mixer, the rotor and the drum rotate in opposite directions. The dry powder materials include one or more of aluminum hydroxide powder, titanium dioxide powder, soluble starch, sesbania powder, etc.
[0010] The raw material intensive mixing unit of the carrier preparation process also includes the step of adding liquid material through the liquid feed hole without changing the stirring speed, and then increasing the rotor speed in the drum to 300-400r / min, and the drum speed to 100-150r / min under the condition of intensive mixing time of 45-60 minutes. The liquid material is dilute nitric acid in the form of a paste, and the mass concentration of the dilute nitric acid is 2%-5%. The material obtained after the end of the raw material intensive mixing unit is still a powder, and no agglomeration occurs. Among them, the liquid material includes one or more of acidic aluminum sol, alkaline silica sol, alkylphenol polyoxyethylene ether, dilute nitric acid, etc.
[0011] During the carrier preparation process, the rolling into blocks is to pour the powder obtained from the raw material intensive mixing unit into a rolling machine for rolling, the mass ratio of the rolling wheel weight to the powder is preferably 1:1 to 2:1, the rolling speed is preferably 100 to 150 r / min, and the rolling time is 40 to 60 minutes.
[0012] After the rolling block unit of the carrier preparation process is completed, the powder is agglomerated into blocks, and the size of the blocks is preferably 5 to 15 cm.
[0013] In the carrier preparation process, the extrusion molding is to put the block material obtained by rolling into block units into a screw extruder for extrusion molding to obtain wet long strip materials, and the extrusion speed is 2-5 cm / s.
[0014] In the carrier preparation process, the air-drying and curing is to air-dry and cure the wet long strip material obtained by the extrusion molding unit in a well-ventilated place to obtain a dry long strip material, the curing temperature is 20-50° C., and the curing time is 16-24 hours.
[0015] In the carrier preparation process, the high temperature roasting is to roast the dry long strip material obtained by the air-drying curing unit in a continuous mesh belt kiln at a high temperature, the material stacking height on the mesh belt is 3 to 4 cm, the roasting temperature is 500 to 700°C, the roasting time is 5 to 10 hours, and the strip carrier is obtained. After the high temperature roasting unit in the carrier preparation process, the average lateral compressive strength of the strip carrier is 120 to 180 N / cm.
[0016] In the carrier impregnation process, the drum impregnation is to pour the strip-shaped carrier into an intermittent drum, and then pour the impregnation liquid of the metal precursor into the drum to impregnate the carrier.
[0017] The metal is selected from one or more of chromium, molybdenum, tungsten, copper, gold, silver, manganese, rhenium, zirconium, hafnium, cobalt, rhodium, iridium, gallium, indium, thallium, lanthanum and cerium.
[0018] The metal precursor is one or more of metal nitrate, metal acid ammonium salt and metal carboxylate. For example, the metal precursor can be one or more of copper nitrate trihydrate, lanthanum nitrate hexahydrate, ammonium tungstate pentahydrate, ammonium molybdate tetrahydrate, chromium nitrate nonahydrate, cobalt nitrate hexahydrate, zirconium oxynitrate dihydrate, manganese nitrate, ammonium chloroaurate trihydrate, silver nitrate, ammonium perrhenate, tetrabutylammonium tetrachlorohafnium oxide, rhodium hexanoate, ammonium chloroiridate hexahydrate, gallium nitrate, indium nitrate tetrahydrate, thallium nitrate trihydrate, and cerium ammonium nitrate dihydrate.
[0019] The composition of the catalyst involved in the present invention can be found in documents such as CN106140139A, CN106140149A, CN106140178A, CN111774064A, CN114471556A, CN114471591A, CN106140186A, CN106140148A, CN106140191A, and CN114478442A.
[0020] The mass ratio of the impregnation liquid to the strip carrier is preferably 1:1 to 1.4:1, the impregnation vacuum is preferably 0.06 to 0.0.10 MPa, the impregnation temperature is preferably 30 to 50°C, the impregnation time is preferably 30 to 50 minutes, and the drum speed is preferably 2 to 4 r / min. After the impregnation is completed, steam is introduced into the drum jacket to completely evaporate the impregnation liquid while maintaining the drum vacuum and speed unchanged, the evaporation temperature is 90 to 120°C, and the evaporation time is 1 to 2 hours.
[0021] During the carrier impregnation process, the high temperature drying is to dry the carrier obtained by the drum impregnation unit in a drying oven at a drying temperature of 100 to 120° C. for a drying time of 4 to 6 hours.
[0022] During the carrier impregnation process, the high-temperature calcination is to calcine the carrier obtained by the high-temperature drying unit of the carrier impregnation process in a continuous mesh belt kiln to obtain a strip catalyst. The carrier stacking height on the mesh belt is 3 to 4 cm, the calcination temperature is 500 to 800°C, and the calcination time is 4 to 8 hours.
[0023] During the carrier impregnation process, the rolling pelletizing is to pelletize the strip catalyst obtained by the high-temperature roasting unit of the carrier impregnation process in a rolling cutter, and the rotation speed of the rolling cutter is 100-200r / min.
[0024] During the carrier impregnation process, the vibration screening and powder removal is to screen the catalyst obtained from the rolling pelletizing unit in a vibration screening machine to remove the broken and powdered catalyst. The aperture size of the vibration screening machine screen is not higher than the carrier diameter, the proportion of catalyst broken and powdered is 2% to 8%, and the average lateral pressure strength of the catalyst is 120 to 180 N / cm.
[0025] The second aspect of the present invention provides a method for forming a carrier in industrial production, which is characterized by comprising five units: intensive mixing of raw materials, rolling into blocks, extrusion forming, drying and curing, and high-temperature roasting; wherein,
[0026] The raw material intensive mixing is operated using a drum-type intensive mixer containing a rotor. The dry powder material is intensively mixed for 20 to 30 minutes in the drum-type intensive mixer under the conditions that the rotor speed in the drum is 80 to 120 r / min and the drum rotation speed is 60 to 100 r / min, and the rotor and the drum rotate in opposite directions. The raw material intensive mixing unit also includes the steps of adding liquid material through the liquid feed hole without changing the stirring speed, and then increasing the rotor speed in the drum to 300 to 400 r / min and the drum rotation speed to 100 to 150 r / min, and the intensive mixing time is 45 to 60 minutes.
[0027] The rolling into blocks is to pour the powder obtained by the raw material intensive mixing unit into a rolling machine for rolling, the mass ratio of the rolling wheel weight to the powder is 1:1-2:1, the rolling speed is 100-150r / min, and the rolling time is 40-60 minutes; after the rolling into blocks unit is completed, the powder is agglomerated into blocks, and the size of the blocks is 5-15 cm.
[0028] The extrusion molding is to put the block material obtained by rolling into block units into a screw extruder for extrusion molding to obtain wet long strip materials, and the extrusion speed is 2-5 cm / s.
[0029] The air-drying and curing process is to air-dry and cure the wet long strip material obtained by the extrusion molding unit in a well-ventilated place to obtain a dry long strip material, the curing temperature is 20-50° C., and the curing time is 16-24 hours.
[0030] The high temperature roasting is to roast the dry long strip material obtained from the drying and curing unit in a continuous mesh belt kiln at a high temperature, with the material stacking height on the mesh belt being 3 to 4 cm, the roasting temperature being 500 to 700° C., and the roasting time being 5 to 10 hours to obtain a strip carrier.
[0031] The third aspect of the present invention provides a hydrogen peroxide decomposition catalyst prepared according to the first aspect of the present invention.
[0032] The fourth aspect of the present invention provides a method for decomposing hydrogen peroxide in a methanol aqueous solution, characterized by using the hydrogen peroxide decomposition catalyst provided by the third aspect.
[0033] The mass fraction of hydrogen peroxide in the methanol aqueous solution is 0.02-1.0%. The method is carried out in a fixed bed reactor, and the feed mass space velocity of the methanol aqueous solution is 1-10h -1 , the reaction temperature is 20-100°C.
[0034] The present invention has the following advantages: the mixing effect of dry powder raw materials and liquid raw materials is higher, the amount of dilute nitric acid used in the paste making agent is greatly reduced, and the emission of nitrogen oxides during the roasting process can be reduced. The kneading effect is better, and the carrier strength obtained under the same conditions is higher; the mesh belt kiln roasting can achieve continuous production, and the ventilation is good, which can reduce the roasting temperature and time; the impregnation degree is more uniform, the catalyst deactivation rate is slowed down, and the catalyst life is longer. DETAILED DESCRIPTION
[0035] The present invention will be further described below by way of examples.
[0036] In all embodiments and comparative examples, the side pressure crushing strength of the catalyst was measured using a ZQJ-Ⅱ intelligent particle strength testing machine produced by Dalian Intelligent Testing Machine Factory, with reference to HG / T2782-1996 standard. The measured side pressure crushing strength was the average value of 3 to 5 groups of 25 catalyst particles per group.
[0037] Example 1
[0038] This embodiment illustrates the method for forming the carrier provided by the present invention.
[0039] Step 1: Add 900 grams of aluminum hydroxide split (produced by Shandong Zibo Taiguang Chemical Co., Ltd.), 1300 grams of titanium dioxide powder (produced by Guangdong Guanghua Technology Co., Ltd.), 400 grams of soluble starch (produced by Guangdong Guanghua Technology Co., Ltd.), and 100 grams of field sesame powder (produced by Fushun Shengfei Chemical Co., Ltd.) into a drum-type intensive mixer (produced by Ailixu Co., Ltd.) containing a rotor. The rotor speed in the drum is 100r / min, the drum speed is 80r / min, the intensive mixing time is 30 minutes, and the rotor and the drum rotate in opposite directions to carry out intensive mixing of the dry powder materials. After the dry powder materials are mixed evenly, the rotation speed is maintained unchanged, and liquid materials are added through the liquid feed hole, which are 1800 grams of acidic aluminum sol (produced by Hunan Jianchang Petrochemical Co., Ltd.), 150 grams of octylphenol polyoxyethylene ether-15 (produced by Guangdong Guanghua Technology Co., Ltd.), and 500 grams of dilute nitric acid (for making ointments, mass fraction 2%). Then the rotor speed in the drum is increased to 350r / min, and the drum speed is increased to 120r / min. The intensive mixing time is 60 minutes. The directions of the rotor and the drum are opposite, and the dry powder material and the liquid material are vigorously mixed. The final product is still a powder material, and no material agglomeration is seen.
[0040] Step 2: Spread the vigorously mixed materials evenly in the roller compactor. The roller mass is 10kg, the compaction speed is 120r / min, and the compaction time is 60 minutes. After compaction, the powder material will be clumped into blocks with a maximum size of no more than 15cm.
[0041] Step 3: The crushed block material is put into a screw extruder for extrusion molding. The extrusion diameter is 2.2 mm and the extrusion speed is 4 cm / s.
[0042] Step 4: Dry and cure the wet long strips obtained by extrusion in a well-ventilated place at a curing temperature of 30°C for 18 hours, and obtain a hard long strip after the curing.
[0043] Step 5: The dried long strips obtained by curing are roasted at high temperature in a continuous mesh belt kiln. The material stacking height on the mesh belt is 4 cm, the roasting temperature is 600°C, and the roasting time is 6 hours to obtain a strip carrier. The average lateral compression strength of the strip carrier is 125N / cm.
[0044] Example 2
[0045] This example illustrates the preparation method of the strip-shaped composite metal oxide hydrogen peroxide decomposition catalyst provided by the present invention.
[0046] Step 1: Pour 2500 grams of the strip carrier prepared in Example 1 into an intermittent drum. Then prepare 1500 grams of ammonium molybdate tetrahydrate aqueous solution (the mass of ammonium molybdate tetrahydrate is 300 grams) and 1500 grams of copper nitrate trihydrate aqueous solution (the mass of copper nitrate trihydrate is 300 grams), and pour the two impregnation solutions into the drum respectively. The impregnation vacuum degree is 0.08MPa, the impregnation temperature is 30°C, the impregnation time is 40 minutes, and the drum speed is 4r / min. After the impregnation is completed, the vacuum degree and speed of the drum are maintained unchanged, and then steam is introduced into the drum jacket to completely evaporate the impregnation solution. The evaporation temperature is 100°C and the evaporation time is 2 hours. At this time, the carrier obtained is uniform blue.
[0047] Step 2: Dry the obtained carrier in a drying oven at a drying temperature of 100° C. for 6 hours.
[0048] Step 3: The obtained carrier is calcined at high temperature in a continuous mesh belt kiln. The stacking height of the carrier on the mesh belt is 3 cm, the calcination temperature is 800°C, and the calcination time is 5 hours to obtain a strip catalyst with a khaki surface and a light cyan core.
[0049] Step 4: The obtained strip catalyst is pelletized in a rolling cutter with a rotation speed of 120 r / min.
[0050] Step 5: The catalyst obtained by pelletizing is screened out in a vibrating screen to remove the broken and powdered catalyst. The aperture size of the vibrating screen is 1.6 mm. The proportion of broken and powdered catalyst is 5%. The average lateral pressure strength of the catalyst is 128 N / cm.
[0051] Example 3
[0052] This example illustrates the decomposition reaction method of hydrogen peroxide in methanol aqueous solution provided by the present invention.
[0053] The catalyst obtained in Example 2 was loaded into a fixed bed reactor to decompose hydrogen peroxide in a methanol aqueous solution. The mass fraction of methanol was 48%, the mass fraction of hydrogen peroxide was 0.5%, and the feed mass space velocity of the methanol aqueous solution was 8h -1, the reaction temperature was 65° C. The hydrogen peroxide concentration at the outlet of the fixed bed reactor was analyzed by a hydrogen peroxide titrator (Metrohm, Switzerland). When the hydrogen peroxide concentration at the outlet exceeded 0.02%, the corresponding reaction time was the service life of the catalyst, which was 280 hours.
[0054] Comparative Example 1
[0055] This comparative example illustrates the formation of a comparative carrier.
[0056] The operations are performed according to steps 1 to 5 in Example 1, except that no strong mixing is performed during the operation of step 1, and a multifunctional catalyst forming machine (produced by the Science and Technology Industrial General Factory of South China University of Technology) is used to mix the dry powder material and the wet powder material. The forming machine has a fixed hopper, an internal paddle speed of up to 60 r / min, and an amount of dilute nitric acid (mass fraction 2%) added to the paste is 850 g. The average lateral compression strength of the obtained strip carrier is 120 N / cm.
[0057] Comparative Example 2
[0058] This comparative example illustrates the formation of a comparative carrier.
[0059] The operations were performed according to steps 1 to 5 in Example 1, except that a roller was not used in step 2, but a multifunctional catalyst forming machine (produced by the Science and Technology Industrial General Factory of South China University of Technology) was used to knead the powder into blocks. The maximum kneading speed of the paddle was 60 r / min, and the amount of dilute nitric acid (mass fraction 2%) added to the paste was 850 g. The average lateral compression strength of the obtained strip carrier was 100 N / cm.
[0060] Comparative Example 3
[0061] This comparative example illustrates the formation of a comparative carrier.
[0062] The steps 1 to 5 in Example 1 were followed, except that the step of rolling into blocks in step 2 was omitted, and the vigorously mixed powder was directly extruded into strips in the extruder in step 3. The average lateral compressive strength of the obtained strip carrier was 75 N / cm.
[0063] Comparative Example 4
[0064] This comparative example illustrates the formation of a comparative carrier.
[0065] The operations were performed according to steps 1 to 5 in Example 1, except that the air-drying and curing in step 4 was omitted, and the wet long strip material was directly calcined at high temperature. The average strength of the obtained strip carrier was 60 N / cm.
[0066] Comparative Example 5
[0067] This comparative example illustrates the formation of a comparative carrier.
[0068] The operations were performed according to steps 1 to 5 in Example 1, except that the high-temperature calcination device in step 5 was replaced with a muffle furnace. The average strength of the obtained strip carrier was 80 N / cm.
[0069] Comparative Example 6
[0070] This comparative example illustrates the formation of a comparative carrier.
[0071] The steps 1 to 5 in Example 1 were followed, except that the high-temperature calcination device in step 5 was replaced with a muffle furnace, the calcination temperature was increased to 700°C, and the calcination time was extended to 12 hours. The average strength of the obtained strip carrier was 122 N / cm.
[0072] Comparative Example 7
[0073] This comparative example illustrates the preparation of a comparative catalyst.
[0074] The operation is carried out according to step 1 to step 5 of Example 2, except that the drum impregnation in step 1 is changed to static immersion impregnation, that is, the carrier is mixed with the impregnation liquid and then allowed to stand at normal pressure for 12 hours. After the impregnation liquid solution is evaporated to dryness, the carrier is blue but the color is different in depth. After roasting, the light impregnation color is light cyan, and the dark impregnation color is yellow.
[0075] Comparative Example 8
[0076] This comparative example illustrates the preparation of a comparative catalyst.
[0077] The operations were carried out according to steps 1 to 5 of Example 2, except that the high-temperature calcination device in step 3 was changed to a muffle furnace, and the calcination time was extended to 12 hours.
[0078] Comparative Example 9
[0079] This example illustrates the decomposition reaction process of hydrogen peroxide in aqueous methanol using a comparative catalyst.
[0080] The life of the comparative catalyst of Comparative Example 7 was evaluated according to Example 3. The service life of the comparative catalyst was 200 hours.
[0081] By comparing the molding process of the carrier in Example 1 with the molding process of the comparative carrier obtained in Comparative Example 1, it can be seen that when a traditional molding machine and kneading machine are used to mix and stir the materials, due to the low stirring rate, a strong mixing of the dry powder material and the liquid material cannot be achieved. Therefore, it is more difficult for the water molecules in the liquid material to enter the dry powder material. Therefore, more ointment-making agent dilute nitric acid (mass fraction 2%) needs to be added to knead into a mass, resulting in more nitrogen oxides being emitted during the carrier roasting process.
[0082] Comparing the molding process of the carrier in Example 1 with the molding process of the comparative carrier obtained in Comparative Example 2, it can be seen that when the conventional molding machine and kneading machine are used to knead the materials into blocks, due to the low kneading speed, more paste-forming agent dilute nitric acid (mass fraction 2%) needs to be added to knead into a mass, resulting in more nitrogen oxides being emitted during the carrier roasting process. In addition, the kneading effect of the roller is better, and the obtained carrier has higher strength.
[0083] By comparing the forming process of the carrier in Example 1 with the forming process of the comparative carrier obtained in Comparative Example 3, it can be seen that the powder material after intensive mixing of dry powder material and liquid material can also be directly extruded, but the strength of the obtained carrier is very low, indicating that the powder material must be kneaded after intensive mixing to improve the carrier strength.
[0084] Comparing the forming process of the carrier in Example 1 with the forming process of the comparative carrier obtained in Comparative Example 4, it can be seen that the wet long strip material after extrusion has a high water content, and the water evaporates rapidly when directly subjected to high-temperature roasting, resulting in a loose carrier with very low strength, which cannot meet the strength requirements of industrial fixed bed loading. This shows that air-drying and curing is an indispensable key step of the present invention.
[0085] By comparing the forming process of the carrier in Example 1 with the forming process of the comparative carrier obtained in Comparative Examples 5 to 6, it can be seen that since the carrier raw material contains more organic matter, after the roasting equipment is replaced from a mesh belt kiln with good ventilation to a sealed muffle furnace, a higher roasting temperature and a longer roasting time are required to achieve the same carrier strength, resulting in higher energy consumption during the roasting process.
[0086] By comparing the process of impregnating the carrier with metal to obtain the catalyst in Example 2 with the impregnation process of the comparative catalyst obtained in Comparative Example 7, it can be seen that after the carrier impregnation process is changed from dynamic impregnation with a rotary drum under vacuum to static impregnation under normal pressure, the time required for impregnation is prolonged and the degree of impregnation is uneven, resulting in different colors of the metal oxide on the surface of the carrier after calcination under the same conditions.
[0087] By comparing the process of impregnating the carrier with metal to obtain the catalyst in Example 2 with the impregnation process of the comparative catalyst obtained in Comparative Example 8, it can be seen that after the roasting equipment is replaced from a mesh belt kiln with good ventilation to a sealed muffle furnace, a longer roasting time is required to achieve the same roasting effect, resulting in higher energy consumption during the roasting process.
[0088] Comparison of the results of the decomposition reaction method of hydrogen peroxide in methanol aqueous solution in Example 3 and Comparative Example 9 shows that since the catalyst obtained by static impregnation has an uneven degree of impregnation, the active metal oxide species on the surface will aggregate, and the aggregated metal oxide species will be lost faster. Therefore, the catalyst prepared in Comparative Example 7 in Comparative Example 9 has a shorter service life.
[0089] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0090] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0091] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a strip-shaped composite metal oxide hydrogen peroxide decomposition catalyst suitable for industrial production, comprising a carrier preparation process and a carrier impregnation process; characterized in that: The carrier preparation process includes five units: strong mixing of raw materials, rolling into blocks, extrusion molding, drying and curing, and high-temperature roasting; wherein the strong mixing of raw materials is carried out using a drum-type strong mixer with a rotor; The carrier impregnation process includes five units: drum impregnation, high temperature drying, high temperature roasting, rolling granulation, and vibration screening to remove powder.
2. The method according to claim 1, characterized in that In the carrier preparation process, the raw materials are vigorously mixed by mixing the dry powder materials in a drum-type intensive mixer for 20 to 30 minutes under the conditions of a rotor speed of 80 to 120 r / min and a drum rotation speed of 60 to 100 r / min; in the drum-type intensive mixer, the rotor and the drum rotate in opposite directions.
3. The method according to claim 2, characterized in that The dry powder material includes one or more of aluminum hydroxide powder, titanium dioxide powder, soluble starch, and sesbania powder.
4. The method according to claim 2, characterized in that The intensive mixing of the raw materials during the carrier preparation process also includes the step of adding liquid material through the liquid feed hole without changing the stirring speed, and then increasing the rotor speed in the drum to 300-400r / min and the drum speed to 100-150r / min for 45-60 minutes.
5. The method according to claim 4, characterized in that The liquid material includes one or more of acidic aluminum sol, alkaline silica sol, alkylphenol polyoxyethylene ether, and dilute nitric acid.
6. The method according to claim 1, characterized in that The rolling into blocks in the carrier preparation process is to pour the powder obtained from the raw material intensive mixing unit into a rolling machine for rolling, the mass ratio of the rolling wheel weight to the powder is 1:1 to 2:1, the rolling speed is 100 to 150 r / min, and the rolling time is 40 to 60 minutes.
7. The method according to claim 6, characterized in that After the rolling into blocks unit is completed in the carrier preparation process, the powder material is agglomerated into blocks, and the size of the blocks is 5 to 15 cm.
8. The method according to claim 1, characterized in that In the carrier preparation process, the extrusion molding is to put the block material obtained by rolling into block units into a screw extruder for extrusion molding to obtain wet long strip materials, and the extrusion speed is 2-5 cm / s.
9. The method according to claim 1, characterized in that In the carrier preparation process, the air-drying and curing is to air-dry and cure the wet long strip material obtained by the extrusion molding unit in a well-ventilated place to obtain a dry long strip material, the curing temperature is 20-50° C., and the curing time is 16-24 hours.
10. The method according to claim 1, characterized in that The high temperature roasting in the carrier preparation process is to roast the dry long strip material obtained from the drying and curing unit in a continuous mesh belt kiln at a high temperature, with the material stacking height on the mesh belt being 3 to 4 cm, the roasting temperature being 500 to 700° C., and the roasting time being 5 to 10 hours to obtain a strip carrier.
11. The method according to claim 10, characterized in that After the high-temperature calcination unit in the carrier preparation process, the average lateral compression strength of the strip-shaped carrier is 120-180 N / cm.
12. The method according to claim 1, characterized in that The drum impregnation in the carrier impregnation process is to pour the strip-shaped carrier into an intermittent drum, and then pour the impregnation aqueous solution containing the metal precursor into the drum to impregnate the carrier.
13. The method according to claim 12, characterized in that The metal is selected from one or more of chromium, molybdenum, tungsten, copper, gold, silver, manganese, rhenium, zirconium, hafnium, cobalt, rhodium, iridium, gallium, indium, thallium, lanthanum and cerium.
14. The method according to claim 12, characterized in that The metal precursor is one or more of metal nitrate, metal ammonium salt and metal carboxylate.
15. The method according to claim 12, characterized in that The metal precursor is one or more of copper nitrate trihydrate, lanthanum nitrate hexahydrate, ammonium tungstate pentahydrate, ammonium molybdate tetrahydrate, chromium nitrate nonahydrate, cobalt nitrate hexahydrate, zirconium oxynitrate dihydrate, manganese nitrate, ammonium chloroaurate trihydrate, silver nitrate, ammonium perrhenate, tetrabutylammonium tetrachlorohafnium oxide, rhodium hexanoate, ammonium chloroiridate hexahydrate, gallium nitrate, indium nitrate tetrahydrate, thallium nitrate trihydrate, and ammonium cerium nitrate dihydrate.
16. The method according to claim 12, characterized in that The mass ratio of the impregnation liquid to the strip carrier is 1:1-1.4:1, the impregnation vacuum is 0.06-0.10 MPa, the impregnation temperature is 30-50° C., the impregnation time is 30-50 minutes, and the drum speed is 2-4 r / min.
17. The method according to claim 12, characterized in that After the impregnation is completed, steam is introduced into the drum jacket to completely evaporate the impregnation liquid while maintaining the vacuum degree and rotation speed of the drum unchanged. The evaporation temperature is 90-120° C. and the evaporation time is 1-2 hours.
18. The method according to claim 1, characterized in that The high temperature drying in the carrier impregnation process is to dry the carrier obtained by the drum impregnation unit in a drying oven at a drying temperature of 100 to 120° C. for a drying time of 4 to 6 hours.
19. The method according to claim 1, characterized in that The high temperature calcination in the carrier impregnation process is to calcine the carrier obtained by the high temperature drying unit of the carrier impregnation process in a continuous mesh belt kiln to obtain a strip catalyst. The carrier stacking height on the mesh belt is 3 to 4 cm, the calcination temperature is 500 to 800°C, and the calcination time is 4 to 8 hours.
20. The method according to claim 1, characterized in that The rolling pelletizing in the carrier impregnation process is to pelletize the strip catalyst obtained by the high-temperature roasting unit in the carrier impregnation process in a rolling cutter, and the rotation speed of the rolling cutter is 100-200r / min.
21. The method according to claim 1, characterized in that The vibration screening and powder removal in the carrier impregnation process is to screen out the broken and powdered catalyst from the catalyst obtained by the rolling pelletizing unit in a vibration screening machine.
22. The method according to claim 21, characterized in that In the vibrating screen powder removal unit of the carrier impregnation process, the aperture size of the vibrating screen is not higher than the carrier diameter, the proportion of catalyst crushing and powdering is 2% to 8%, and the average lateral pressure strength of the catalyst is 120 to 180 N / cm.
23. A method for forming a carrier in industrial production, characterized in that: It includes five units: strong mixing of raw materials, rolling into blocks, extrusion molding, drying and curing, and high-temperature roasting. The raw materials are vigorously mixed using a drum-type intensive mixer with a rotor. The dry powder material is vigorously mixed for 20 to 30 minutes in the drum-type intensive mixer at a rotor speed of 80 to 120 r / min and a drum speed of 60 to 100 r / min. In the drum-type intensive mixer, the rotor and the drum rotate in opposite directions. The rolling into blocks is to pour the powder obtained by the raw material intensive mixing unit into a rolling machine for rolling, the mass ratio of the rolling wheel weight to the powder is 1:1-2:1, the rolling speed is 100-150r / min, and the rolling time is 40-60 minutes; Extrusion molding is to put the block material obtained by rolling into block units into a screw extruder for extrusion molding to obtain wet long strip materials, and the extrusion speed is 2 to 5 cm / s; Drying and curing is to dry and cure the wet long strip material obtained by the extrusion molding unit in a well-ventilated place to obtain a dry long strip material, the curing temperature is 20-50°C, and the curing time is 16-24 hours; High temperature roasting is to roast the dry long strip material obtained from the drying and curing unit in a continuous mesh belt kiln at high temperature. The material stacking height on the mesh belt is 3 to 4 cm, the roasting temperature is 500 to 700°C, and the roasting time is 5 to 10 hours to obtain a strip carrier.
24. The method for forming a carrier according to claim 23, characterized in that: The raw material intensive mixing unit also includes the steps of adding liquid material through the liquid feed hole without changing the stirring speed, and then increasing the rotor speed in the drum to 300-400 r / min and the drum speed to 100-150 r / min for 45-60 minutes.
25. The method for forming a carrier according to claim 23, characterized in that: After the rolling into blocks unit is completed, the powder material is agglomerated into blocks, and the size of the blocks is 5 to 15 cm.
26. A hydrogen peroxide decomposition catalyst obtained by the preparation method according to any one of claims 1 to 22.
27. A method for decomposing hydrogen peroxide in methanol aqueous solution, characterized in that The hydrogen peroxide decomposition catalyst of claim 26 is used.
28. The method according to claim 27, characterized in that The mass fraction of hydrogen peroxide in the methanol aqueous solution is 0.02-1.0%.
29. The method according to claim 28, characterized in that The method is carried out in a fixed bed reactor, and the feed mass space velocity of the methanol aqueous solution is 1 to 10 h -1 , the reaction temperature is 20-100°C.
Citation Information
Patent Citations
Catalyst for decomposing hydrogen peroxide and application method
CN106140139A
Catalyst and hydrogen peroxide decomposition method
CN106140148A
Catalyst and method for decomposing hydrogen peroxide
CN106140149A
Catalyst for decomposing hydrogen peroxide and method for decomposing hydrogen peroxide in epoxidation reaction product
CN106140178A
Decomposition catalyst and method for decomposing hydrogen peroxide in epoxidation reaction product through same
CN106140186A